IN PRINCIPLES OF SPIRITUAL AND EDUCATIONAL ACTIVITY IN THE STUDENT'S ACTIVITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on the principles of spiritual and educational activities, explains its role in the development of the student's personality. Also, some aspects of the organization of spiritual and educational activities in higher education institutions are explained.